2021
DOI: 10.3390/agriculture11020119
|View full text |Cite
|
Sign up to set email alerts
|

Response of Interspecific Geraniums to Waste Wood Fiber Substrates and Additional Fertilization

Abstract: Promotion of sustainable horticulture via wider use of peat substrate substitutes makes wood fiber an increasingly popular substrate component. Interspecific geraniums are plants of huge potential in the floriculture market, but there are not enough specific guidelines on their cultivation. This study investigated the effectiveness of enriching peat substrate with 10%, 20%, 30%, or 40% (by volume) waste wood fiber in the pot cultivation of interspecific geraniums cv. ‘Calliope Dark Red’. It also examined plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Future studies with a balanced design may provide more robust information on substrate performance. Previous work has shown that the addition of nitrogen fertilizer to wood fiber substrates can ameliorate negative impacts on growth (Gruda and Schnitzler, 1999;Zawadzi nska et al, 2021). It is possible that the low fertilizer rates used in the study enhanced the differential effects of this substrate compared with bark and peat.…”
Section: Discussionmentioning
confidence: 92%
“…Future studies with a balanced design may provide more robust information on substrate performance. Previous work has shown that the addition of nitrogen fertilizer to wood fiber substrates can ameliorate negative impacts on growth (Gruda and Schnitzler, 1999;Zawadzi nska et al, 2021). It is possible that the low fertilizer rates used in the study enhanced the differential effects of this substrate compared with bark and peat.…”
Section: Discussionmentioning
confidence: 92%
“…The values of SPAD depend significantly on the nutrition of plants with nitrogen [24,25]. In the study conducted by Zawadzińska et al [26] the highest leaf greenness index was noted in interspecific pelargonium cultivated in peat enriched with 20% of wood fiber. However, Wolna-Maruwka et al [11] and Wróblewska et al [27,28] stated that SPAD depends on the compost composition and its percentage in the substrate used for plant cultivation.…”
Section: Discussionmentioning
confidence: 94%
“…Others plants revealed a similar number of inflorescences when compared with the control. According to the literature, the influence on the flowering process is significantly dependent on the species, compost composition and its percentage in the substrate [11,23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, plants grown in 0% compost exhibited better growth than those in the other applications. Effects of growing media on flowering process and plant growth are highly dependent on species, compost composition and percentage (Wolna-Maruwka et al, 2017;Zawadzińska et al, 2021;Schroeter-Zakrzewska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%